A role for gamma-delta T cells in theileriosis - Daubenberger, C.A. (International Laboratory for Research on Animal Diseases, 1995)
T cells bearing the gamma-delta antigen can constitute up to 50% of T cells in peripheral blood and lymphoid organs of calves below six months of age. This observation prompted us to investigate the involvement of gamma-delta T cells in the immune response of yound calves against Theileria parva.